Impact of Chronic Inflammation, Assessed by hs-CRP, on the Association between Red Cell Distribution Width and Arterial Cardiovascular Disease: The Tromsø Study - Lappegård, Jostein; Ellingsen, Trygve S.; Hindberg, Kristian; Mathiesen, Ellisiv B.; Njølstad, Inger; Wilsgaard, Tom; Løchen, Maja-Lisa; Brækkan, Sigrid K.; Hansen, John-Bjarne (TH Open, 2018)
Red cell distribution width (RDW), a measure of variability in size of circulating erythrocytes, is associated with arterial cardiovascular disease (CVD), but the underlying mechanism remains unclear. We aimed to investigate the impact of chronic inflammation as measured by high-sensitivity C-reactive protein (hs-CRP) on this relationship, and explore whether RDW could be a mediator in the causal pathway between inflammation and arterial CVD. Baseline characteristics, including RDW and hs-CRP, were obtained from 5,765 individuals attending a population-based cohort study. We followed up participants from inclusion in the fourth survey of the Tromsø Study (1994/1995) until December 31, 2012. Multivariable Cox-regression models were used to calculate hazard ratios (HR) with 95% confidence intervals (CI) for incident myocardial infarction (MI) and ischemic stroke across quintiles of hs-CRP and RDW. Subjects with hs-CRP in the highest quintile had 44% higher risk of MI (HR: 1.44, 95% CI: 1.14–1.80), and 64% higher risk of ischemic stroke (HR: 1.64, 95% CI: 1.20–2.24) compared with subjects in the lowest quintile. RDW mediated 7.2% (95% CI: 4.0–30.8%) of the association between hs-CRP and ischemic stroke. Subjects with RDW in the highest quintile had 22% higher risk of MI (HR: 1.22, 95% CI: 0.98–1.54) and 44% higher risk of ischemic stroke (HR: 1.44, 95% CI: 1.06–1.97) compared with subjects in the lowest quintile. These risk estimates were slightly attenuated after adjustments for hs-CRP. Our findings suggest that chronic inflammation is not a primary mechanism underlying the relationship between RDW and arterial CVD.
Keywords: epidemiology; myocardial infarction; stroke; blood cells; risk factors